ANTIBACTERIAL ACTIVITY OF KARAMUNTING (RHODOMYRTUS TOMENTOSA (AITON) HASSK) LEAF EXTRACT AND FRACTIONS - Sinulingga, Siska Esperanza; Hasibuan, Poppy Anjelisa Zaitun; Suryanto, Dwi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: This study was to analyze the karamunting leaf extract and fractions effectiveness against Staphylococcus aureus and Pseudomonas aeruginosa infection. Methods: Phytochemical screening is done in the extract and fractions of karamunting leaf continue with Standard agar well diffusion method for S. aureus and P. aeruginosa. Dimethyl sulfoxide was used as negative control, and standard antibiotic Kalmicetine (chloramphenicol) was used as positive control. Result: The ethyl acetate fraction showed the highest antibacterial activity against S. aureus and P. aeruginosa. Conclusion: Karamunting leaf can be used to treat the bacterial infection diseases especially infection from S. aureus and P. aeruginosa.